1999
DOI: 10.1046/j.1365-2745.1999.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

The density dependence of plant responses to elevated CO2

Abstract: Summary0 Stands of the annual Brassica kaber were grown at a range of six densities in both ambient and elevated CO 1 environments\ and measurements of shoot growth were made from seedling emergence through to reproduction[ 1 Early in stand development "10 days following emergence#\ CO 1 enhancement "b# for above!ground biomass was highly density!dependent\ ranging from 0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 35 publications
1
29
1
Order By: Relevance
“…The few previous studies of density · CO 2 effects on more than one aspect of growth have shown enhancements to root and shoot mass (Berntson et al 2000 Frequency distributions for (a) shoot (stem + leaf), (b) root, and (c) reproductive biomass size-classes. Open and shaded bars represent ambient (360 lL L À1 ) and enriched (720 lL L À1 ) CO 2 concentrations, respectively vegetative and reproductive mass (Ackerly et al 1995;He et al 2003;Wayne et al 1999), but we know of no other studies that address growth stimulation in all plant structures, or the reduction of whole-plant biomass inequalities within densely grown populations or communities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The few previous studies of density · CO 2 effects on more than one aspect of growth have shown enhancements to root and shoot mass (Berntson et al 2000 Frequency distributions for (a) shoot (stem + leaf), (b) root, and (c) reproductive biomass size-classes. Open and shaded bars represent ambient (360 lL L À1 ) and enriched (720 lL L À1 ) CO 2 concentrations, respectively vegetative and reproductive mass (Ackerly et al 1995;He et al 2003;Wayne et al 1999), but we know of no other studies that address growth stimulation in all plant structures, or the reduction of whole-plant biomass inequalities within densely grown populations or communities.…”
Section: Discussionmentioning
confidence: 99%
“…In natural plant populations, the growth advantages of large individuals over smaller ones can be either enhanced or reduced (Poorter et al 2003;Wayne et al 1999) by the extra carbon supply in elevated atmospheric CO 2 . The resulting increase or decrease in size inequalities can in turn affect the relative reproductive output of dominant and subordinate plants (He et al 2003;Wayne et al 1999), potentially altering evolutionary and population dynamics (Thomas et al 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in canopy architecture (Wetzel & van der Valk 1998), the timing of the main phase of competition (Wray & Strain 1987), and the responses induced by varying plant density (Wayne et al 1999) are among the most important factors influencing the outcome of plant competition. In this study, yield at harvest after 1 yr growth provides a useful snapshot of the interactions of the 2 species, demonstrating the trends in relation to treatment discussed above, and suggesting that competition is mediated by plant height and rhizome development.…”
Section: Discussionmentioning
confidence: 99%
“…influence both the magnitude and duration of the responses of tree seedlings and saplings to CO 2 (Callaway et al, 1994). The results presented here and those obtained in earlier studies (Wayne et al, 1999;Wayne and Bazzaz, 1995) suggest that the estimates of the CO 2 fertilization potential of forest species, derived from individually grown trees may be unreliable for trees like birch that commonly regenerate in the presence of competition. Therefore, it is necessary to simultaneously consider density when assessing accurately the responses of plant populations to CO 2 enrichment.…”
mentioning
confidence: 50%